Ectopic Thyroid Tissue in the Mediastinum Characterized by Histology and Functional Imaging with I-123 SPECT/CT - Jed Hummel; Jason Wachsmann; Kelley Carrick; Orhan K. Oz; Dana Mathews; Fangyu Peng (Case Reports in Radiology)
Ectopic thyroid tissue is a rare entity and when discovered it is typically along the pathway of embryologic migration of the thyroid. We present a case of incidental finding of ectopic thyroid tissue within mediastinum in a 61-year-old female patient with a history of total thyroidectomy for thyroiditis and nodules. The patient presented to emergency room with cough and right chest pain and underwent a chest computed tomographic angiogram (CTA) to exclude pulmonary embolism as part of chest pain workup. One right paratracheal mediastinal soft tissue nodule was visualized on the images of CTA. This right paratracheal soft tissue mass was found to be ectopic benign thyroid tissue by histological analysis of the biopsied tissue samples. The function of this ectopic thyroid tissue was characterized by I-123 radioiodine uptake and single photon emission computed tomography/computed tomography (SPECT/CT) imaging. This case illustrates that ectopic thyroid tissue should be included for differential diagnosis of a hyperdense soft tissue mass located within mediastinum. I-123 SPECT/CT is useful for guiding tissue biopsy of ectopic thyroid tissue distant from orthotopic thyroid gland and functional and anatomic characterization of mediastinal ectopic thyroid tissue for surgical resection when it is medically necessary.